Deskripsi Keterkaitan Peran Guru Dengan Perilaku Sosial Anak di TK Dewi Sartika Kec,Sipatana Kota Gorontalo - Sulisti Virya Saman; Sri Wahyuningsi Laiya; Sri Rawanti (Inovasi Pendidikan dan Anak Usia Dini, 2024)
This study aims to determine the correlation between the teacher's role and children's social behavior at TK Dewi Sartika Kindergarten, Sipatana District, Gorontalo City. The researcher employed a qualitative research method to explore this relationship. The subjects consisted of one teacher and 13 students from the same class. Data were collected through observation, interviews, and documentation. The data analysis techniques include data reduction, data presentation, and conclusion. The results describe that the correlation between the teacher's role and the social behavior of young children encompasses six aspects: 1) The teacher as an educator, for example, teaches children how to make friends, share, and collaborate through group games or class activities. 2) The teacher as a manager, for example, establishing clear classroom rules, such as taking turns speaking during discussions or respecting others' feelings. 3) The teacher, as a supervisor, guides children to resolve conflicts peacefully and teaches them how to negotiate or empathize with their peers' emotions. 4) The teacher is an innovator, for example, introducing role-play activities where children pretend to be in different professions or social situations, allowing them to practice social interactions fun and innovatively. 5) The teacher is a communicator, for example, helping children express their emotions healthily when they feel angry or sad and teaching them how to communicate with their peers. 6) The teacher is a motivator, for example, by praising and rewarding children who display positive social behavior, such as collaborating in teams, helping friends in need, or constructively resolving conflicts. This helps children feel more motivated to continue improving their social skills.